Cryo-EM structures of GnRHR: Foundations for next-generation therapeutics - Shiyi Shen; Xinheng He; Heng Liu; Wen Hu; H. Eric Xu; Jia Duan (Proceedings of the National Academy of Sciences, 2025)
Gonadotropin-releasing hormone receptor (GnRHR) is critical for reproductive health and a key therapeutic target for endocrine disorders and hormone-responsive cancers. Using high-resolution cryoelectron microscopy, we determined the structures of Sus scrofa and Xenopus laevis GnRHRs bound to mammal GnRH, uncovering conserved and species-specific mechanisms of receptor activation and G protein coupling. The conserved “U”-shaped GnRH conformation mediates high-affinity binding through key interactions with residues such as K 3.32 , Y 6.51 , and Y 6.52 . Species-specific variations in extracellular loops and receptor–ligand contacts fine-tune receptor function, while ligand binding induces structural rearrangements, including N terminus displacement and TM6 rotation, critical for signaling. Structure–activity relationship analysis demonstrates how D-amino acid substitutions in GnRH analogs enhance stability and receptor affinity. Distinct binding modes of agonists and antagonists elucidate mechanisms of ligand-dependent activation and inactivation. These insights lay the groundwork for designing next-generation GnRHR therapeutics with enhanced specificity and efficacy for conditions like endometriosis, prostate cancer, and infertility.